Prediction of the catalytic site of single-atom Ni catalyst using the hydrogen evolution reaction as a model platform - Choi, Hansol; Kim, Dong Hyun; Han, Man Ho; Oh, Hyung-Suk; Heo, Jinseo; Lim, Hyung-Kyu; Choi, Chang Hyuck (Pergamon Press Ltd., 2022)
NiNC catalysts, in which Ni ions are atomically dispersed by ligation with nitrogen functionalities on a carbon support, have received considerable attention owing to their promising activity in the electrochemical reduction of CO2 to CO. However, a poor catalytic activity has been theoretically predicted for the conventional metalloporphyrin-like catalytic moieties, symmetric Ni-N-4. This has led to extensive debate regarding the nature of the actual catalytic site. In this study, we prepare five MeNC catalysts (Me = Cr, Mn, Fe, Co, or Ni) with predominant Me-N-4 moieties and measure their hydrogen evolution reaction (HER) activities. A linear correlation is identified between the HER activity and the theoretically predicted hydrogen binding energy (HBE) of all the symmetric Me-N-4 models, except for Ni-N-4. Thus, various coordination structures are further considered as catalytic Ni sites. Based on the combination of experimental and theoretical approaches, we conclude that coordinately unsaturated Ni sites can be present, which are responsible for the considerable electrocatalytic activity of the NiNC.